Realitas Komunikasi Diantara Penganut Umat Berbeda Agama: Studi Kasus Etnis Tionghoa Dan Jawa Serang Di Kecamatan Kasemen Kawasan Banten Lama: Studi Kasus Etnis Tionghoa dan Jawa Serang di Kecamatan Kasemen Kawasan Banten Lama - Wawan Setiawan; Mega Febriyanti; Nurbaiti Arifiana (An-Nahdliyyah: Jurnal Studi Keislaman, 2023)
The reality of communication between adherents of different religions and ethnic Chinese and Javanese in Indonesia. This research was conducted to understand how social interaction between groups of different religions and ethnicities takes place in a heterogeneous society. This research method is descriptive in the form of a case study. A case study is a research that includes an assessment aimed at providing a detailed description of the background, nature and characteristics of a case, in other words, a case study focuses attention on a case intensively and in detail. The results of this study indicate that the reality of communication among adherents of different religions (Chinese and Serang Javanese Ethnicity) in Kasemen District, Banten Lama Region) is very good: (1) People who have awareness of the existence of similarities or equal differences, awareness of people who are aware that there is no ethnicity or religion that is higher and nobler but all are the same or equal, (3) Patterns of communication intercultural activities occur when deliberation activities and mutual cooperation activities are carried out in Kp. Pamarican which is used as a meeting place and carries out various activities in the environment, (3) Acculturation which appears in terms of the culture adopted but there is mixing with other cultures and does not leave their original culture, (4) Chinese Ethnicity and Serang Javanese Ethnicity need each other, just like the Avalokistevara Vihara needs workers of Serang Javanese ethnicity because Chinese ethnic workers are very minimal due to the migration of ethnic Chinese people out of town, as well as Serang Javanese people need jobs to fulfill their lives and (5) The practice of multiculturalism in Kp. In general, Pamarican is good in the daily practice of several Chinese informants when interacting with Javanese Serang residents. The multicultural nature of the people is able to create conditions and situations that are orderly, understand each other, respect each other and respect one another.